Impact of English Language Coaching Classes in Pakistan: Bridging Educational Gaps and Socioeconomic Challenges - Zohaib Hassan Sain; Hui Geng; Yumei Song (WISE Pendidikan Indonesia, 2024)
The education system in Pakistan faces challenges in effectively teaching English as a second language, prompting students to seek external support through coaching classes. This studyexplores the impact and implications of coaching classes on English language learning, examining their influence on academic performance and their emergence as a parallel education system. A mixed-method approach was adopted, utilizing surveys of 300 participants, in-depth interviews with 30 students, teachers, and parents, and classroom observations conducted in 10 schools and coaching centers. Quantitative analysis revealed that 75% of students attended coaching classes, with significant academic improvements in English performance noted for coached students compared to non-coached students (p < 0.05). Qualitative findings highlighted both the benefits and challenges: while coaching classes offer personalized attention and enhance exam preparation, they also impose a financial burden on families and reflect inadequacies in formal education. The study concludes that while coaching significantly enhances students’ English skills, it underscores the need for improvements within schools to provide more comprehensive language education. Addressing gaps in formal education could reduce over-reliance on coaching classes, ensuring more equitable access to language learning opportunities.